Solid state hydrogen storage container based on phase change material
Patent Information
- Application Number
- CN202522300348.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-30
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2035-10-30
AI Technical Summary
[0004]本实用新型为了解决上述问题,提出了一种基于相变材料的固态储氢容器,本实用新型通过传热肋片强化了相变材料与储氢材料之间的热量传递,解决了现有技术中温度分布不均、传热效率低的问题,提升了储氢容器的稳定性和效率
本实用新型在储氢容器主体的外壁内设置有夹层,夹层内设置有相变材料,夹层内间隔设置有多个传热肋片;采用相变材料发生相变时吸收或释放潜热的特征,代替了电加热元件或冷却系统实现升温和降温的方式,在夹层内间隔设置有多个传热肋片,借助传热肋片强化了相变材料与储氢材料之间的热量传递,解决了现有技术中温度分布不均、传热效率低的问题,提升了储氢容器的稳定性和效率。
Smart Images

Figure CN224836968U_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solid-state hydrogen storage technology, specifically relating to a solid-state hydrogen storage container based on phase change materials. Background Technology
[0002] Hydrogen energy, as an efficient, clean, and renewable energy source, has attracted widespread attention. Solid-state hydrogen storage, with its advantages of high hydrogen storage density and good safety, has become one of the most promising hydrogen storage methods. Solid-state hydrogen storage materials exhibit significant thermal effects during hydrogen absorption and release. During hydrogen absorption, the storage material reacts chemically with hydrogen gas, releasing a large amount of heat and causing the temperature inside the container to rise; during hydrogen release, the reaction requires the absorption of heat, which in turn lowers the temperature inside the container.
[0003] Traditional technologies typically employ electric heating elements or cooling systems to achieve heating and cooling in order to meet the temperature requirements for hydrogen absorption and release. However, these methods suffer from drawbacks such as high energy consumption, complex structure, high cost, and difficult maintenance, making it difficult to meet the demands of practical applications for efficient, energy-saving, and reliable hydrogen storage equipment. While the latent heat absorption or release characteristics of phase change materials (PCMs) during phase change can replace electric heating elements or cooling systems for heating and cooling, existing solid-state hydrogen storage containers based on PCMs suffer from uneven temperature distribution and low heat transfer efficiency. Utility Model Content
[0004] To address the aforementioned problems, this invention proposes a solid-state hydrogen storage container based on phase change materials. This invention enhances the heat transfer between the phase change material and the hydrogen storage material through heat transfer fins, solving the problems of uneven temperature distribution and low heat transfer efficiency in the prior art, and improving the stability and efficiency of the hydrogen storage container.
[0005] According to some embodiments, this utility model provides a solid hydrogen storage container based on phase change material, adopting the following technical solution: A solid hydrogen storage container based on phase change material includes a hydrogen storage container body and a hydrogen storage material disposed within the hydrogen storage container body; The outer wall of the hydrogen storage container body is provided with a sandwich layer, and a phase change material is provided in the sandwich layer; multiple heat transfer fins are arranged at intervals in the sandwich layer.
[0006] Furthermore, the main body of the hydrogen storage container includes an inner liner and an outer shell; the hydrogen storage material is disposed in the inner liner; the outer shell is fitted over the outer liner, and the interlayer is located between the outer shell and the inner liner.
[0007] Furthermore, a heat-conducting layer is provided inside the inner liner.
[0008] Furthermore, one end of the heat transfer fin is connected to the heat-conducting layer, and the other end extends into the phase change material in a three-level branching manner.
[0009] Furthermore, the heat transfer ribs include primary ribs, secondary ribs, and tertiary ribs; the primary ribs are distributed along the circumference of the inner liner at a first preset angle, the secondary ribs are perpendicular to the outer wall of the inner liner, and the tertiary ribs branch off from the secondary ribs at an angle lower than the preset angle.
[0010] Furthermore, the thermally conductive layer is a graphene coating.
[0011] Furthermore, the outer layer of the phase change material is paraffin wax, and the inner layer is a sodium nitrate-potassium nitrate eutectic salt.
[0012] Furthermore, the hydrogen storage material is configured as a hollow spherical solid hydrogen storage material.
[0013] Furthermore, a heat insulation layer is provided on the outside of the outer shell.
[0014] Furthermore, the hydrogen storage container body is provided with a first connection port and a second connection port at both ends.
[0015] Compared with the prior art, the beneficial effects of this utility model are as follows: This invention features a sandwich layer within the outer wall of the hydrogen storage container body, containing a phase change material and multiple heat transfer fins spaced apart within the sandwich layer. Utilizing the latent heat absorption or release characteristic of the phase change material during phase change, it replaces electric heating elements or cooling systems for heating and cooling. The multiple heat transfer fins spaced apart within the sandwich layer enhance heat transfer between the phase change material and the hydrogen storage material, solving the problems of uneven temperature distribution and low heat transfer efficiency in existing technologies, and improving the stability and efficiency of the hydrogen storage container. Attached Figure Description
[0016] The accompanying drawings, which form part of this specification, are used to provide a further understanding of this utility model. The illustrative embodiments of this utility model and their descriptions are used to explain this utility model and do not constitute an improper limitation of this utility model.
[0017] Figure 1 This is a cross-sectional structural diagram of the container of this utility model.
[0018] The components include: 1. Hydrogen storage container body; 2. Hydrogen storage material; 3. Phase change material; 4. Temperature sensor; 5. First connection port; 6. Second connection port; 7. Inner liner; 8. Outer shell; 9. Interlayer; 10. Thermal conductive layer; 11. Thermal insulation layer; 12. Heat transfer fins. Detailed implementation method: The present invention will be further described below with reference to the accompanying drawings and embodiments.
[0019] It should be noted that the following detailed description is illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0020] like Figure 1 As shown, one embodiment provides a solid hydrogen storage container based on phase change material, including a hydrogen storage container body 1, a hydrogen storage material 2, a phase change material layer 3, and heat transfer fins 12, etc.
[0021] The main body 1 of the hydrogen storage container includes an inner liner 7 and an outer shell 8; the inner liner 7 is used to contain the hydrogen storage material 2, and the outer shell 8 is fitted outside the inner liner 7, with a sandwich 9 formed between the two.
[0022] The inner liner 7 is provided with a heat-conducting layer 10; the heat-transferring ribs 12 are disposed in the space 9, one end of the heat-transferring ribs 12 is connected to the heat-conducting layer 10 on the outer wall of the inner liner 7, and the other end extends into the phase change material 3 in a three-level branching manner.
[0023] The heat transfer fins 12 include primary fins, secondary fins, and tertiary fins; the primary fins are distributed at 30° (first preset angle) along the circumference of the inner liner 7 (branching at a 30° angle from the secondary fins), the secondary fins are perpendicular to the outer wall of the inner liner 7, and the tertiary fins branch at a 45° angle (second preset angle) from the secondary fins, forming a "spider web" heat transfer network. The heat transfer fins 12 can be made of copper, and the total heat exchange area is increased compared to traditional straight fins.
[0024] The hydrogen storage container body 1 has a first connection port 5 and a second connection port 6 at both ends, which can be connected to corresponding pipes for the entry and exit of hydrogen. The hydrogen storage material 2 can be configured as a hollow spherical solid hydrogen storage material, such as hollow spherical magnesium hydride. Using a hollow spherical hydrogen storage material can improve the efficiency of hydrogen storage.
[0025] The outer shell 8 is provided with a heat insulation layer to improve the heat preservation capacity of the hydrogen storage container body 1.
[0026] The phase change material 3 is filled within the space 9. The phase change material 3 can be a composite phase change material: the outer layer is paraffin wax, and the inner layer is sodium nitrate-potassium nitrate eutectic salt, separated by a porous metal mesh, which is adapted to the temperature range of hydrogen absorption and desorption of the hydrogen storage material.
[0027] In this embodiment, a design employing two phase change materials (paraffin wax as the outer layer and sodium nitrate-potassium nitrate eutectic salt as the inner layer) separated by a porous metal mesh aims to leverage the different phase change temperature ranges and latent heat characteristics of the two materials to achieve synergistic effects, thereby avoiding the failure of a single phase change material due to temperature exceeding its phase change range. It should be noted that paraffin wax, as an organic phase change material, typically operates in the ambient temperature range of 40-70℃, with a phase change heat of approximately 200 kJ / kg. Sodium nitrate-potassium nitrate eutectic salt, on the other hand, is an inorganic phase change material with a relatively higher phase change temperature. When the hydrogen storage device operates, it undergoes processes such as hydrogen addition and release, which involve the generation and absorption of heat, causing changes in the internal temperature of the device.
[0028] During operation, the hydrogen addition process releases heat during hydrogen adsorption, causing the temperature of the main body of the hydrogen storage container 1 to rise. Because the outer paraffin layer has a low phase change temperature, it first absorbs heat and undergoes a phase change, transitioning from a solid to a liquid state. In this process, the paraffin absorbs a large amount of latent heat, thus reducing the temperature rise around the hydrogen storage container. As the hydrogen addition process continues, if the temperature rises further beyond the phase change range of the paraffin, the inner sodium nitrate-potassium nitrate eutectic salt begins to function. The sodium nitrate-potassium nitrate eutectic salt continues to absorb the increased heat and undergoes a phase change, transitioning from a solid to a liquid state. It continues to absorb heat, maintaining the temperature around the hydrogen storage container within a relatively suitable range. This prevents the hydrogen storage reaction from being affected by excessively high temperatures and also prevents the single phase change material (such as paraffin) from becoming unable to effectively absorb heat due to temperatures exceeding its phase change range, thus avoiding temperature runaway.
[0029] Hydrogen release process: During hydrogen release, heat needs to be absorbed to promote hydrogen desorption. At this time, the two phase change materials, which are already in a liquid state, begin to release heat. First, the relatively high-temperature inner sodium nitrate-potassium nitrate eutectic salt releases heat to the hydrogen storage module. When the temperature drops to the phase change range of paraffin, paraffin also begins to release latent heat, continuously providing the hydrogen storage container with the heat required for hydrogen release. This synergistic effect ensures that even if the temperature changes during the hydrogen release process, there is always a phase change material that can provide heat, avoiding the situation where the hydrogen release process is hindered because the temperature of a single phase change material exceeds its phase change range and cannot effectively provide heat.
[0030] During hydrogen storage, heat is transferred outwards, creating a temperature gradient. The outer paraffin layer initially contacts the lower-temperature environment; its lower phase transition temperature allows it to absorb heat at lower temperatures, initially stabilizing the temperature. As the temperature rises, the inner sodium nitrate-potassium nitrate eutectic salt takes effect at higher temperatures. This distribution of phase change material according to the temperature gradient fully utilizes heat across different temperature ranges, improving the efficiency of heat management. Paraffin has good chemical stability, low density and cost, and its phase transition characteristics at room temperature meet the initial temperature regulation requirements of hydrogen storage containers under normal operating conditions. Meanwhile, the sodium nitrate-potassium nitrate eutectic salt has a higher latent heat of phase transition and a higher phase transition temperature, enabling it to absorb or release a large amount of heat at higher temperatures, compensating for the shortcomings of paraffin in the high-temperature range. The complementary properties of both provide a more comprehensive and stable temperature regulation capability for hydrogen storage devices.
[0031] During heat conduction, the thermal resistance from the hydrogen storage container to the external environment needs to be carefully controlled. While paraffin has relatively low thermal conductivity, when used as an outer layer material, it can slow down heat loss to the external environment to some extent, providing a degree of insulation. Meanwhile, the inner layer of sodium nitrate-potassium nitrate eutectic salt is more similar to the hydrogen storage material, and its relatively good thermal conductivity helps to quickly absorb or transfer the heat generated or needed by the hydrogen storage material, ensuring effective heat transfer and utilization within the container.
[0032] In this embodiment, the porous metal mesh serves to separate the two phase change materials. The porous metal mesh has a pore structure with pore sizes ranging from 10 to 100 micrometers in diameter. This ensures efficient heat conduction between the two phase change materials while preventing large-scale mixing of the liquid phase change materials. Taking a pore diameter of 50 micrometers as an example, this size is smaller than the critical surface tension value of paraffin and sodium nitrate-potassium nitrate eutectic salt in their liquid states. The surface tension of the two materials is sufficient to form a stable meniscus within the pores, making it difficult for liquid paraffin to penetrate to the eutectic salt side, and the eutectic salt liquid cannot easily enter the paraffin region, effectively preventing large-scale mixing. Simultaneously, the 50-micrometer pore size does not disrupt the overall continuity of the metal mesh, allowing for efficient heat transfer between the two phase change materials through the metal framework. The excellent conductor properties of the metal mesh itself make the pores' obstruction to heat conduction negligible. Paraffin wax and sodium nitrate-potassium nitrate eutectic salt, as two different substances, possess different surface tensions and wettability to porous metal meshes. Paraffin wax, being an organic compound, exhibits surface tension due to intermolecular forces. When in contact with the porous metal mesh, this surface tension prevents the liquid paraffin wax from easily penetrating through the pores into the sodium nitrate-potassium nitrate eutectic salt region on the other side. Similarly, the sodium nitrate-potassium nitrate eutectic salt liquid also possesses its own surface tension and wettability. The different surface properties of these two materials prevent them from easily permeating and mixing through the porous metal mesh in their liquid state.
[0033] The density of paraffin wax is generally between 0.89 g / cm³ and 0.94 g / cm³, while the density of sodium nitrate-potassium nitrate eutectic salt is different. In the liquid state, due to the density difference, even if a small number of liquid molecules approach the pores of the porous metal mesh, they will be unable to overcome their own gravity and surface tension due to buoyancy caused by density differences, and will instead enter the phase change material region on the other side through the pores, thus further reducing the possibility of mixing of the two phase change materials.
[0034] The heat-conducting layer 10 on the inner wall of the inner liner 7 is a graphene coating, which is in close contact with the hollow spherical magnesium hydride, rapidly transferring the heat generated by the hydrogen storage material 2 to the outer wall of the inner liner 7. The heat insulation layer 11 on the outer surface of the outer shell 8 can be configured as a composite structure of vacuum insulation board and fiberglass cloth to reduce heat exchange between the container and the outside environment.
[0035] In some embodiments, a temperature sensor 4 is provided inside the hydrogen storage container body 1. The temperature sensor 4 can be a distributed optical fiber sensor, and multiple temperature sensors 4 can be provided to achieve temperature detection.
[0036] The working principle of this embodiment is as follows: Hydrogen absorption process: The hydrogen storage material reacts with hydrogen, releasing heat. This heat is transferred to the outer wall of the inner liner 7 through the graphene thermal conductive layer, and then rapidly introduced into the phase change material 3 by the heat transfer fins 12. The phase change material 3 absorbs heat and undergoes a phase change, changing from a solid to a liquid state. The multi-level branched structure of the heat transfer fins 12 evenly distributes the heat throughout the entire phase change material 3, preventing excessively high local temperatures in the inner liner.
[0037] Hydrogen release process: Magnesium hydride decomposes and absorbs heat, phase change material 3 releases latent heat, phase change material 3 changes from liquid to solid, and heat is quickly conducted to the inner liner 7 through the reverse transfer path of heat transfer fins 12, and then evenly transferred to the hollow spherical magnesium hydride through the graphene heat-conducting layer to maintain the temperature required for the reaction.
[0038] This invention utilizes phase change materials for heating and cooling, eliminating the need for external energy supply, thus reducing energy consumption and costs, and avoiding the problems associated with complex equipment use and maintenance. The "spider web" network of fractal heat transfer fins increases the heat exchange area, significantly improving the heat transfer rate compared to flat fins, shortening the hydrogen absorption and desorption reaction time, and significantly improving heat transfer efficiency. The synergistic effect of the composite phase change material and fractal fins keeps the internal temperature difference of the hydrogen storage material within a small range, solving the problem of large temperature gradients in conventional methods and optimizing temperature uniformity. The phase change material layer consists of two phase change materials separated by a porous metal mesh. The latent heat of phase change of the two materials can work synergistically, avoiding the failure of a single phase change material due to temperature exceeding its phase change range. The thermally conductive layer on the inner wall of the liner improves heat transfer efficiency, enabling the phase change material to respond to temperature changes more quickly; the heat insulation layer on the outer surface of the shell reduces heat exchange with the external environment, further improving temperature control. Compared to solid particles, hollow spherical hydrogen storage materials have a hollow structure that effectively reduces the density of the material and lightens the overall weight of the hydrogen storage system. The geometry of the spheres allows for more compact and uniform packing within the container, improving space utilization. The internal cavity can accommodate the volume expansion that occurs during hydrogen absorption and desorption, reducing interparticle compression and extending the material's lifespan. Furthermore, the hollow structure facilitates rapid heat transfer, making the reaction faster and more efficient.
[0039] The above description is merely a preferred embodiment of this utility model and is not intended to limit the utility model. Various modifications and variations can be made to this utility model by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this utility model should be included within the protection scope of this utility model.
Claims
1. A solid-state hydrogen storage container based on phase change materials, characterized in that, It includes a hydrogen storage container body and a hydrogen storage material disposed within the hydrogen storage container body; The outer wall of the hydrogen storage container body is provided with a sandwich layer, and a phase change material is provided in the sandwich layer; multiple heat transfer fins are arranged at intervals in the sandwich layer.
2. The solid-state hydrogen storage container based on phase change material as described in claim 1, characterized in that, The hydrogen storage container body includes an inner liner and an outer shell; the hydrogen storage material is disposed in the inner liner; the outer shell is fitted over the outer liner, and the interlayer is located between the outer shell and the inner liner.
3. The solid-state hydrogen storage container based on phase change material as described in claim 2, characterized in that, The inner liner is equipped with a heat-conducting layer.
4. The solid-state hydrogen storage container based on phase change material as described in claim 3, characterized in that, One end of the heat transfer fin is connected to the heat-conducting layer, and the other end extends into the phase change material in a three-level branching manner.
5. The solid-state hydrogen storage container based on phase change material as described in claim 4, characterized in that, The heat transfer fins include primary fins, secondary fins and tertiary fins; the primary fins are distributed at a first preset angle along the circumference of the inner liner, the secondary fins are perpendicular to the outer wall of the inner liner, and the tertiary fins branch off from the secondary fins at an angle lower than the preset angle.
6. The solid-state hydrogen storage container based on phase change material as described in claim 3, characterized in that, The thermally conductive layer is a graphene coating.
7. The solid-state hydrogen storage container based on phase change material as described in claim 1, characterized in that, The outer layer of the phase change material is paraffin wax, and the inner layer is sodium nitrate-potassium nitrate eutectic salt.
8. The solid-state hydrogen storage container based on phase change material as described in claim 1, characterized in that, The hydrogen storage material is configured as a hollow spherical solid hydrogen storage material.
9. The solid-state hydrogen storage container based on phase change material as described in claim 2, characterized in that, The outer shell is provided with a heat insulation layer.
10. The solid-state hydrogen storage container based on phase change material as described in claim 1, characterized in that, The hydrogen storage container body is provided with a first connection port and a second connection port at both ends.